A vacancy-engineered Ce-doped NiCo-LDH electrode material for efficient, selective, and stable groundwater defluorination in FCDI systems - Xingtian Wang; Xinyue Jiang; Pengcheng Tang; Junfeng Zhu; Yuwen Wang; Huiqin Li; Dan He; Yuxuan Ma; Yuhan Qin; Boping Ren; Xiaojing Wang (Chemical Engineering Journal, 2026)

Co-sorption of arsenic and fluoride using the hierarchical Mg-La-Fe nanosheets derived from layered double oxides - Xingtian Wang; Junfeng Zhu; Liang Qi; Yuhan Qin; Boping Ren; Xiaojing Wang (Chemical Engineering Journal, 2024)

Electrocoalescence of W/O emulsions in electric fields generated by matrix electrodes - Lingbo Huang; Ling Chen; Ping OuYang; Boping Ren (Journal of Water Process Engineering, 2023)

Downregulation of Circ-CEP128 Enhances the Paclitaxel Sensitivity of Cervical Cancer Through Regulating miR-432-5p/MCL1 - Ying Zhao; Yi Lan; Yugang Chi; Boping Yang; Chunyan Ren (Biochemical Genetics, 2022)

Warming exacerbates the impact of nutrient enrichment on microbial functional potentials important to the nutrient cycling in shallow lake mesocosms - Lijuan Ren; Yuanyuan Liu; Torben L. Lauridsen; Martin Søndergaard; Boping Han; Jianjun Wang; Erik Jeppesen; Jizhong Zhou; Qinglong L. Wu (Limnology and Oceanography, 2021)
Shallow lakes, the most numerous waterbodies on Earth, are susceptible to climate warming and nutrient enrichment whose effects on the microbial functional potentials are not yet fully understood, however. Here, we applied a microarray‐based technology termed GeoChip 5.0 to investigate microbial functional genes at the beginning of April in shallow lake ecosystems simulated in mesocosms that have been undergoing nutrient enrichment and warming for 9 yr. Our results showed that warming exacerbated the impact of nutrient enrichment on microbial metabolic potentials and significantly elevated the microbial autotrophy potentials, carbon degradation potentials (e.g., starch, hemicellulose, cellulose, and chitin), and polyphosphate mobilization potentials. We also observed that warming enhanced the impacts of nutrient enrichment on microbial functional gene structure. The combination of warming and nutrient enrichment increased the deterministic effect from phytoplankton, causing higher interlinking of microbial functional genes involved in the carbon, nitrogen, phosphorus, and sulfur cycling in correlation‐based networks. Overall, we propose that the joint effect of warming and nutrient enrichment promoted the autotrophic carbon supply and the heterotrophic carbon demand and changed the carbon fluxes in the experimental mesocosms.

Phytoplankton assemblages in a complex system of interconnected reservoirs: the role of water transport in dispersal - Ren Hu; Xueke Duan; Liang Peng; Boping Han; Luigi Naselli-Flores (Hydrobiologia, 2017)

Comparing biological classifications of freshwater phytoplankton: a case study from South China - Ren Hu; Boping Han; Luigi Naselli-Flores (Hydrobiologia, 2013)